(NsOC(Bi(NOLOG(Bi(NQ (B:s (NNAW^ALXNIJ POS(Bi(NBNIK (B/s - (NqKUBA(B, (NoLENA oLEKSANDR)QÆWNA(B,s)E ((NhARK)QÆW (B:s)E (NkONSTANTA(B,s, 1996)
(Nw NAW^ALXNOMU POS)QÆBNIKU WIKLADENÆ OSNOWNÆ PROBLEMI Æ POLOVENNQ ZAGALXNOÇ SOCÆOLOGÆ^NOÇ TEORÆÇ(B.s)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NsOC)QÆOLOGÆQs)E; (NSTRUKTURA SOC(Bi(NOLOG(Bi)QÇs)E; (NSTRUKTURA SUSP)QÆLXSTWAs)E; (NKULXTURAs; (NOSOBIST(Bi(NSTXs; (NEKONOM(Bi(NKAs; (NS(Bi(NM(B'(NQs; (NPOL(Bi(NTIKAs; (NOSW(Bi(NTAs; (NSOC)QÆALXNIJ ÆNSTITUTs)E; (NOSOBIST)QÆSTXs)E; (NGROMADSXKA DUMKAs; (NSOC)QÆOLOGÆ^NIJ ANALÆZs)E